Human herpesvirus-6, varicella-zoster virus and oligoclonal bands in demyelinating diseases of the central nervous system - Nicklén, Jenna (University of Helsinki, 2016)
Tiivistelmä suomeksi.
Keywords: herpesvirukset; infektiot; hermoston taudit; MS-tauti; keskushermosto